Crystal structure of an Lrs14‐like archaeal biofilm regulator from Sulfolobus acidocaldarius. Issue 11 (2nd November 2018) - Vogt, Marian S.; Völpel, Simon L.; Albers, Sonja-Verena; Essen, Lars-Oliver; Banerjee, Ankan
Abstract : A detailed analysis of a winged helix–turn–helix family transcriptional regulator that positively regulates archaeal biofilm formation is reported. Abstract : The small winged helix–turn–helix (wHTH) proteins of the Lrs14 family are major transcriptional regulators and act as archaeal biofilm regulators (AbfRs) in the crenarchaeote Sulfolobus acidocaldarius . Here, the first crystal structure of an AbfR ortholog, AbfR2, the deletion of which is known to impair biofilm formation, is presented. Like most other wHTH orthologs, AbfR2 is dimeric in solution as well as in its 2.45 Å resolution crystal structure. Given the presence of three independent AbfR2 dimers in the asymmetric unit, the crystal structure shows a considerable degree of conformational variation within the dimer, the antiparallel orientations of which are stabilized by coiled‐coil interaction between H4 helices. Conserved anchor interactions between helices H0 and H4 of AbfR2 further contribute to dimer stabilization. The combined structural and bioinformatic analysis reveals cluster‐specific structural differences between different members of the Lrs14 protein family.